The Beauty of Toba Architecture Living in Harmony with the Surrounding Natural Environment - Sudarwani, Margareta Maria; Widati, Galuh; Bintang, Situmorang Lumay; Simanjuntak, Faran Sere (University of Merdeka Malang, 2022)
Toba architecture is one of the most interesting architectural concepts. Toba architectural house has a charming shape and ornaments equipped with beautiful natural landscapes around it. Nature has a fairly important meaning for the people of Toba Samosir where the relationship and orientation between mountains and lakes become the basic of the layout of their home design. One of the areas that have a Toba architecture style is located on the shores of Lake Toba, Sigumpar Sub district, Toba Samosir Regency, North Sumatra. Environmental arrangements with local wisdom that is strong enough in harmony with the surrounding natural environment, namely mountains and lakes. Jabu houses and Sopo still relatively survive with the style of Toba architecture and have not been affected by modern architecture. Today Toba Architecture is threatened with extinction due to several things which also often the cause of the destruction of hundreds of traditional houses throughout the country. The uniqueness of the Sigumpar Area mentioned above is very interesting to study and research. The purpose of the research is to know the characteristics of Toba architecture in Sigumpar area so that it can be a reference in determining which toba architectural characteristics that need to be maintained in the framework of the preservation. The writing method used is a descriptive method based on empirical facts in the field. In this study the research area is devided in four observation unit/huta which the layout of each observation is varied. The results of this study are expected to provide knowledge about the architectural characteristics of Toba architecture in Sigumpar area and provide concepts related to building preservation and application in designing buildings.